Cancel Culture on Twitter – Cancelling Russians and Ukrainians in the Context of Russian-Ukrainian War - Marsenić, Marija (Sociološki pregled, 2024)
This research deals with the analysis of the phenomenon of cancel culture on the social network Twitter in the context of the Russian-Ukrainian war. Cancel culture as a social phenomenon is becoming increasingly important on social networks, and Twitter has become the key environment for expressing and sharing opinions on this topic. The aim of this research is to understand how Twitter users shape the discourse on cancel culture during the current Russian-Ukrainian war, as well as to assess the intensity of this phenomenon in two different time periods - March 2022 and March 2023. The quantitative-qualitative method of content analysis and discourse analysis was used in the research. The research findings indicate that cancel culture intensified in March 2023 compared to March 2022. The research results highlight that a greater number of tweets were written in a negative tone, manifested in aggressive and insulting comments and sharp polarization into two opposing camps, which corresponds to the characteristic patterns of cancel culture when it comes to Twitter. The use of hashtags has proven to be a powerful tool for promoting ideologies and constructing meaning, enabling the creation of a particular narrative and eliciting connections with like-minded people. The research provides a deeper insight into the dynamics of cancel culture on Twitter in the context of the Russian-Ukrainian war, demonstrating how social and political events shape the perception and opinions of Twitter users.